Fungal Cell Biomass From Enzyme Industry as a Sustainable Source of Hydrocolloids - Nikkilä, Ida; Waldén, Maria; Maina, Ndegwa H.; Tenkanen, Maija; Mikkonen, Kirsi S. (Frontiers in Chemical Engineering, 2020)
Industrial enzyme production yields vast amounts of cell biomass as by-product that is treated as waste, which brings costs and causes an environmental burden. Nonetheless with the current drive towards resource efficiency, conversion of the cell biomass into value-added products would provide an economically viable alternative for the industry. The biomass is composed of fungal cells, containing potentially valuable heteropolysaccharides and glycoproteins, but a technology is lacking to valorize them. For the first time, we characterized the composition of the biomass, extracted biopolymers by aqueous and alkaline treatments, and studied their behavior as novel hydrocolloids in multiphase systems. Alkaline extraction yielded a carbohydrate content of 37.5% and an amino acid content of 27.6%, whereas water extraction yielded 6.6% and 61.3%, respectively. Emulsions prepared with alkaline extracts were relatively stable during a 15-day storage period. We demonstrated that the costly waste management in enzyme production can be replaced by sustainable fractioning, and these fractions can be valorized.